Management Perspectives: Acute Coronary Syndrome in Octogenerians - Ranjan Modi; Sunil Modi (New Frontiers in Medicine and Medical Research Vol. 13, 2021)
Current guidelines for acute coronary syndrome are derived from the data in randomized clinical trials and metanalysis conducted in patients. These patients are generally of younger age. The data of acute coronary syndrome in octogenarians is mainly derived from registries. This mid- and long-term data regarding medical therapy or interventions in octogenarians is low in number with smaller subsets of patients. Most of the physicians are reluctant to use the same guidelines in these elderly patients due to increased chances of complications. This article reviews the available data and literature in acute coronary syndrome in octogenarians and provides management perspectives for these elderly patients. Literature has proved that early invasive protocols seem to be just as feasible in the elderly as in the general population. In order to mitigate any pharmacological side effects, it is imperative to correct the dosages to age- adjusted renal function.